Предмет: Математика,
автор: brnbv29
номер 118 помогите пожалуйста)))
Приложения:
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
1/8 ·⁷√(2¹⁵ax⁵)=2⁻³·⁷√(2¹⁵ax⁵)=⁷√(2⁻²¹·2¹⁵ax⁵)=⁷√(2⁽⁻²¹⁺¹⁵⁾ax⁵)=⁷√((ax⁵)/2⁶)=⁷√((ax⁵)/64)
³√(a⁷·⁴√a)=³√a^(7 +1/4)=³√a^(29/4)=¹²√a²⁹=¹²√(a²⁴a⁵)=a²·¹²√a⁵
⁹√b⁸ ·³√b=b^(8/9 +1/3)=b^(8/9 +3/9)=b^(11/9)=b^(1 2/9)=b·⁹√b²
1/3 ·³√(27·³√x)=3⁻¹·³√(3³√x)=³√(3⁻³·3³√x)=³√(3⁽⁻³⁺³⁾√x)=(x^(1/3))^(1/3)=x^(1/9)=⁹√x
Похожие вопросы
Предмет: Математика,
автор: mariaa4aa
Предмет: Обществознание,
автор: aldyn98
Предмет: Химия,
автор: lysaknadezda05
Предмет: Биология,
автор: лорик30
Предмет: Химия,
автор: Аноним